MENEGAKKAN EVOLUSI PERADABAN BANGSA - Bustami Rahman (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2014)
Although Indonesia suffered from European colonization like most of East Asian countries in the past, its civilizational characteristic is distinct from that of its closest neighbors such as Malaysia, Singapore, and Brunei Darussalam. As a nation, Indonesia is poorer in terms of discipline, law enforcement, and economy. This writing proposes a hypothesis that the cause of such distinction is not the different colonizers. Instead, it is Indonesia?s attitude towards its colonizer that makes it different. In a sense, Malaysia, Singapore, and Brunei Darussalam were “given” freedom by the British Empire, while Indonesia obtained its freedom by force, followed by the removal of all traces of its colonizer, which include the old European values. It was reborn and began its new life as a baby, experiencing multiple dying dots and faltered several times. To survive, Indonesia began its complicated, vicious cycle of involution while its neighbors began their evolution. There are three things that must be done to stop the cycle and enforce an evolutive Indonesian civilization. First, the leaders of this country should learn the reason behind the current poor condition of Indonesia, so they can restrain themselves from making the wrong moves. Second, the implementation of the system should be more repressive at certain times, to enforce discipline and law. Third, it is important to learn that democracy can come in many colors since all nations have different natures and needs.